The effect of teacher direct written corrective feedback on writing of SEGi University Diploma in Hospitality and Management students: a case study / Siti Ummaizah Meor Musa - Meor Musa, Siti Ummaizah (2013)
This study was aimed at investigating how teacher direct written corrective feedback impacted students’ grammatical accuracy in their writing. Besides that, it also looked into how teacher direct written corrective feedback affecting students’ usage of grammatical forms in their writing. Furthermore, the study also aimed at finding the students’ perception towards teacher direct written corrective feedback in their writing. The study employed quasi-experimental research design and the data was obtained from a set of pre-test and posttest and also interview. As indicated from the findings from twenty semester one Diploma in Hospitality and Management students from SEGi University, the results of the study showed that the students of this study bene fitted from teacher direct written corrective feedback and showed improvement in the usage of some grammatical forms which were articles, conjunction and pronoun. The findings also showed that the majority of the students of this study perceived teacher direct written corrective feedback as useful and helpful in helping them in improving their grammatical accuracy in their writing and they want the teacher to continue providing direct written corrective feedback in their writing. The findings were hoped to shed light in the importance of the practice of giving feedback to students’ writing.